Relationships, Knowledge, and Resilience: A Comparative Study of Stakeholder Participation in Great Lakes Areas of Concern - (:unkn) unknown (My University, 2015)
This dissertation investigates the current practices of environmental governance in the Great Lakes region, where at one time the rivers that fed the Great Lakes were choked with debris and on fire. The Great Lakes Water Quality Agreement of 1978 and the 1987 updates inspired collective action to remediate and restore the rivers and nearshore zones of the lakes through the implementation of an ecosystem approach, which included a public participation dimension. While funding and momentum has fluctuated, the constructs – Areas of Concern (AOC), Remedial Action Plans (RAP), and Public Advisory Councils (PAC) persist. In 2010, the Great Lakes Restoration Initiative initiated a flurry of restoration activity throughout the region and revived the AOC process. This study examines several dimensions of activity in the region. First, through a comparative case study of the Milwaukee Estuary, St. Louis River and St. Marys River AOCs this study analyzed how state agencies and local organizations cooperate. Secondly, using a comparative case study of the Michigan and Wisconsin approaches to restoring a beneficial use, this study identified how different approaches to knowledge production could be applied in environmental management. Finally, the study describes how scenario analysis could be applied to produce knowledge across disciplinary natural and social science boundaries to inform Great Lakes policy. The study revealed the organization of Public Advisory Councils and relationships with state agencies created different opportunities for individuals and organizations to participate in the restoration in AOCs. This study also illustrated that rules and institutional constraints shape how knowledge is produced in Areas of Concern, and describes some of the trade-offs involved with engaging citizens in knowledge production. Finally, the Great Lakes Futures Project demonstrated how constructivist learning methodologies can create an inclusionary environment to produce transdisciplinary knowledge for environmental governance. Furthermore, the study suggests the stories created through inductive scenario analysis reflected shared meanings and a new method for integrating political and cultural concerns into socio-ecological systems research. The study will contribute to the literatures about ecosystem-based approaches in the Great Lakes, geographic literature about knowledge production in environmental management, and the understanding of transdisciplinary knowledge production.
Keywords: Aesthetics; Environmental Governance; Great Lakes; Knowledge Production; Resilience; Stakeholder Participation